A Transfer Entropy Approach for the Assessment of the Impact of Inspiratory Muscle Training on the Cardiorespiratory Coupling of Amateur Cyclists - Abreu, Raphael Martins de; Catai, Aparecida Maria; Cairo, Beatrice; Rehder-Santos, Patricia; Silva, Claudio Donisete da; Signini, Étore De Favari; Sakaguchi, Camila Akemi; Porta, Alberto (Frontiers in Physiology, 2020)
The strength of cardiorespiratory interactions diminishes with age. Physical exercise can reduce the rate of this trend. Inspiratory muscle training (IMT) is a technique capable of improving cardiorespiratory interactions. This study evaluates the effect of IMT on cardiorespiratory coupling in amateur cyclists. Thirty male young healthy cyclists underwent a sham IMT of very low intensity (SHAM, n=9), an IMT of moderate intensity at 60% of the maximal inspiratory pressure (MIP60, n=10) and an IMT of high intensity at the critical inspiratory pressure (CIP, n=11). Electrocardiogram, noninvasive photoplethysmographic arterial pressure, and thoracic respiratory movement (RM) were recorded before (PRE) and after (POST) training at rest in supine position (REST) and during active standing (STAND). The beat-to-beat series of heart period (HP) and systolic arterial pressure (SAP) were analyzed with the RM signal via a traditional noncausal approach, such as squared coherence function, and via a causal model-based transfer entropy (TE) approach. Cardiorespiratory coupling was quantified via the HP-RM squared coherence at the respiratory rate (K2HP-RM), the unconditioned TE from RM to HP (TERM→HP) and the TE from RM to HP conditioned on SAP (TERM→HP|SAP). In PRE condition we found that STAND led to a decrease of TERM→HP|SAP. After SHAM and CIP training this tendency was confirmed, while MIP60 inverted it by empowering cardiorespiratory coupling. This behavior was observed in presence of unvaried SAP mean and with usual responses of the baroreflex control and HP mean to STAND. TERM→HP and K2HP-RM were not able to detect the post-training increase of cardiorespiratory coupling strength during STAND, thus suggesting that conditioning out SAP is important for the assessment of cardiorespiratory interactions. Since the usual response of HP mean, SAP mean and baroreflex sensitivity to postural stressor were observed after MIP60 training, we conclude that the post-training increase of cardiorespiratory coupling during STAND in MIP60 group might be the genuine effect of some rearrangements at the level of central respiratory network and its interactions with sympathetic drive and vagal activity.